EKSPERIMENTASI MODEL PEMBELAJARAN TGT DAN NHT DITINJAU DARI ADVERSITY QUOTIENT (AQ) SISWA KELAS VIII SMP NEGERI DI KOTA BANDAR LAMPUNG - Kirana, Arinta Rara (LPPM STKIP PGRI Bandar Lampung, 2017)
This research aims at finding out: (1) which one results better mathematics learning achievement among type TGT, NHT, or conventional; (2) which one has better mathematics learning achievement among students with AQ categories; (3) at each of learning models, which students has better mathematics learning achievement with AQ categories; (4) at each of AQ categories, which one results better mathematics learning achievement among type learning models. This study was quasi-experimental research. The population of this study was all students in grade VII SMPN Bandar Lampung. The sampling technique was done by stratified cluster random sampling. Data analysis tecnique was used to test the hypothesis was twoways analysis of variance with unbalanced cell as a 3x3 factorial design.The conclusions of the research were as follows. (1) Cooperative learning type TGT results better mathematics learning achievement than type NHT and conventional, and the achievement of student mathematics learning by NHT is the same as the achievement conventional. (2) The achievement of student mathematics learning in climbers have the better than the achievement campers, students with climbers have better than mathematics learning achievement quitters, and the achievement of student mathematics learning in campers is the same as the achievement quitters; (3) in each learning models, the students mathematics learning achievment is in constancy with result of AQ categories, (4) in each of AQ categories, students mathematics learning achievment is in constancy with result of learning models.